PENGARUH TRANSFER PRICING, PERTUMBUHAN PENJUALAN, DAN KOMPENSASI EKSEKUTIF TERHADAP TAX AVOIDANCE (Studi Empiris Pada Perusahaan Sektor Energi Sub Sektor Oil, Gas, dan Coal yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021) - Alfiyanti Eka Senjaya; Syamsul Mu’arif (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This study aims to examine the effect of Transfer Pricing, Sales Growth, and Executive Compensation on Tax Avoidance. This study uses a quantitative approach and the data used is secondary data, namely the financial statements of each sample company via the official website www.idx.com. The population in this study are energy sector companies in the oil, gas and coal sub-sector which are listed on the Indonesia Stock Exchange for the 2017-2021 period. Methods in determining the sample using purposive sampling. 11 samples were obtained with a five-year period so that the number obtained was 55 sample data. Testing the data using panel data regression analysis, the selected model selection test is the Common Effect Model with the help of eviews version 9 statistical data processing. The results of this study indicate that Transfer Pricing, Sales Growth and Executive Compensation simultaneously influence Tax Avoidance. Transfer Pricing has an effect on Tax Avoidance. Sales Growth has no effect on Tax Avoidance. Executive Compensation has no effect on Tax Avoidance.